WHAT IS IMPORTANT FOR POSTGRADUATES TO KNOW ABOUT THE ACADEMIC TEXTS? - Nataliya I. Kolesnikova (Высшее образование в России)
This paper is a continuation of a series of articles to assist graduate and postgraduate students of different specialties in writing their own scientific texts of different genres (abstract, article, dissertation, etc). The article considers invariant properties and main category features of scientific texts on the humanities and engineering science. The reasoning about the importance of acquiring the knowledge for a successful presentation of the scientific findings is given.